A Comparative Study of Widows’ Plight in Binwell Sinyangwe’s A Cowrie of Hope and Bayo Adebowale’s Lonely Days - Moussa, SIDI CHABI (Advances in Social Sciences Research Journal, 2020)
The present article aims at making a comparative study of widows’ plight in Binwell Sinyangwe’s A Cowrie of Hope and Bayo Adebowale’s Lonely Days. The plight of African widows is deplorable in African societies where the weight of customs and traditions makes them suffer a lot. In those societies, the maltreatment that men inflict on them is usually inhumane. People even suspect them of being at the origin of their husbands’ death in most cases. Such a situation calls for reflection as it has become a societal problem which deserves a particular attention. Hence the necessity to carry out this research work in order to pinpoint the ins and outs of such a phenomenon through a comparative study of widows’ plight in the selected novels. The methodological approach that I have used in this research work is documentary research. The study has found that the two widows have a similar plight as courageous and resilient women although their situations are not exactly the same in some aspects. The literary theories that I have applied to the study are feminism, a literary theory which aims at revaluing women’s image, and the Marxist critical approach which focusses on class struggle.